Fabrication of low thermal resistance 3C-SiC/diamond structure for GaN epitaxial layer growth - Ryo Kagawa; Yutaka Ohno; Yasuyoshi Nagai; Naoteru Shigekawa; Jianbo Liang (Functional Diamond, 2024)
Integrating diamonds with GaN presents a promising solution for enhancing heat dissipation. However, a critical challenge lies in developing an engineering substrate that facilitates the growth of high-quality GaN epitaxial layers, enabling the production of GaN-based devices with superior thermal management on a large scale. In this study, we have successfully developed an engineering substrate conducive to high-quality GaN growth. This accomplishment was achieved through the direct transfer of a 3 C-SiC thin film, originally grown on Si, to a diamond substrate at room temperature using the surface-activated bonding technique. After the transfer process, we observed the presence of a SiC amorphous layer at the interface, measuring approximately 18.5 nm in thickness. Notably, this thickness reduced to 14.5 nm after annealing at 1100 °C, indicating a transformation from amorphous to polycrystalline SiC due to recrystallization. Furthermore, it is crucial to highlight that no exfoliation of the 3 C-SiC/diamond bonding interfaces was observed even after subjecting them to annealing at 1100 °C. This observation is pivotal for ensuring the high-quality growth of GaN crystals on diamonds. The thermal boundary conductance of the 3 C-SiC/diamond interface reached nearly 93 MW/m2·K, demonstrating significant efficiency for device cooling. These compelling results highlight the potential of the 3 C-SiC/diamond engineering substrate to enable high-performance GaN-based devices, providing significantly enhanced thermal management capabilities. This breakthrough represents a major stride forward in the field.